Growing Concern over Point-of-Care Devices - Canavan, Neil; Sinclair, Heather Q. (MD Conference Express, 2010)
It is increasingly an open question as to when and where point-of-care (POC) glucose meters should be used and what clinical decisions should be made based on POC readings. This article discusses related issues in a dedicated lecture on the subject, as well as implications for for tight glucose control, currently the standard of care in intensive care units.